GLOBALISASI DAN KONSILI VATIKAN II DI ASIA - Johannes Muller (Jurnal Ledalero, 2014)
This paper gives some basic ideas regarding the relationship between globalisation and the Second Vatican Council in Asia as a starting point for more detailed studies in the future. The first part discusses the situation of the churches at the edge of Asian societies and Asian socio-cultural contexts as influenced by globalisation. Then some social concerns are outlined such as poverty, authoritarian regimes and ecological dangers where the church and Asian societies encounter each other. Church engagement in these issues is justified by reference to a number of Counciliar documents such as the Gaudium et spes Constitution and the Diginitatis humanae Declaration. The final part outlines a number of problems such as inculturation, inter-religious dialogue and religious-cultural dialogue. The author emphasises that this paper is not a theological evaluation, but rather a sociological one. Kata-kata Kunci: globalisasi, Konsili Vatikan II, Asia, Gereja, konteks sosio-budaya, pembangunan.